Sistem Pakar untuk Mendiagnosa Gangguan pada Sistem Hepatobiliaris Berbasis Android Mobile - Redo Abeputra Sihombing (Universitas Indraprasta PGRI Jakarta, 2018)
Disturbances in the Hepatobiliaris system are health problems that are often encountered, even growing, so to know the diagnosis will be difficult. A better way is to consult an expert or an expert doctor. But there are also weaknesses such as working hours or limited experts. Expert system is one branch of artificial intelligence that learns how to adopt the way an expert thinks in solving a problem and make decisions and conclusions. The problem discussed is how to design a system that can be used to solve the above problems. The purpose and objective of the author in making this expert sisem is to assist the prospective physician in diagnosing disorders of the Hepatobiliaris system like an expert. Expert system using Best First Search method and using Forward Chaining technique. In this system poured knowledge of an expert in the can during research at Permata Ibu Hospital. An expert system developed based on Android on the client side, PHP and MySQL. This expert system displays a selection of symptoms that can be selected by the user, where each choice of symptoms that will lead the user to the next symptom option to get the conclusion.